Penerapan Rocket Stove dalam Upaya Reduksi Sampah dan Peningkatan Kesadaran Lingkungan Masyarakat Desa Ngalian - Herman Sambodo; Fitrah Amalia Kartika; Ela Nurfazriyah; Jovanka Michelle Artamevia; Vina Nur Aprilliani; Ius Arkarino (Universitas Pahlawan Tuanku Tambusai, 2026)
The increasing amount of waste in rural communities has become a problem that needs to be addressed effectively and sustainably. One solution that can be implemented is the use of a rocket stove, a simple stove that utilizes biomass waste such as twigs, dry leaves, and organic waste as fuel. The rocket stove implementation program in Ngalian Village aims to reduce waste volume, enhance the utilization of waste as an alternative energy source, and raise community awareness about the importance of environmental conservation. The methods used include socialization activities, training on how to build a rocket stove, and assistance in its use. The expected outcomes are a reduction in improperly discarded organic waste, increased community knowledge about waste management, and the development of environmentally friendly behavior. Therefore, the rocket stove can serve as an appropriate and practical solution to support waste management and improve environmental awareness in rural communities.